Our Changing Menu Climate Change and the Foods We Love and Need - Hoffmann, Michael P.; Eisemann, Danielle L.; Koplinka-Loehr, C. (Carrie Ann) (Comstock Publishing Associates, 2021)
Whether you're a chef, baker, distiller, restaurateur, or someone who simply enjoys a good pizza or drink, it's time to come to terms with how climate change is affecting our diverse and interwoven food system. Michael P. Hoffmann, Carrie Koplinka-Loehr and Danielle L. Eiseman offer an eye-opening journey through a complete menu of before-dinner drinks and salads, main courses and sides and coffee and dessert. Along the way they examine the escalating changes occurring to the flavours of spices and teas, the yields of wheat, the vitamins in rice and the price of vanilla.